Improper Technique of Eye Drop Instillation Leading to Corneal Ulcer in a Visually Impaired Glaucoma Patient / Azhan A … [et al.] - A, Azhan 2 ,; E, Zunaina; MK, Khairidzan; SS, Fatimah; Akhtar Ali, Ahmad-Nurfahmi (Universiti Teknologi MARA Cawangan Selangor, 2018)
We report a case of visually impaired glaucoma patient with long term use of topical glaucoma medications presented with a corneal ulcer due to the improper technique of eye drop instillation. A 70-year-old gentleman with advanced primary open angle glaucoma (POAG) on his right eye and absolute glaucoma on his left eye, presented with painful redness and purulent discharge of the right eye for two weeks. He was using four types of topical glaucoma medication on his right eye since failed trabeculectomy two years ago. His right eye vision was 6/24 and painless blindness of the left eye before the presentation. He was administering all the medications himself despite his current vision status. Right eye examination showed visual acuity of 3/60 with clinical features of corneal ulcer. During the observation of his eye drop instillation technique, he consistently touched the tip of the bottle to his right cornea. The corneal contact area corresponded to the corneal ulcer area and size. In addition to this, the culture result obtained from both corneal ulcer and the bottles’ tips yielded similar microorganism which was Staphylococcus aureus. After an intensive course of topical antibiotics treatment, the corneal ulcer healed with a scar and the vision improved to 6/24 from 3/60. Although this incident is rare, it is crucial for the treating physicians to address the issue properly and co-manage these patients with pharmacists and nursing staffs as well as to seek support from the caretakers to prevent this blinding complication.